Adipocyte Fatty Acid-Binding Protein Promotes Palmitate-Induced Mitochondrial Dysfunction and Apoptosis in Macrophages - Li, Hui; Xiao, Yang; Tang, Lin; Zhong, Feng; Huang, Gan; Xu, Jun-Mei; Xu, Ai-Min; Dai, Ru-Ping; Zhou, Zhi-Guang (Frontiers in Immunology, 2018)
A high level of circulating free fatty acids (FFAs) is known to be an important trigger for macrophage apoptosis during the development of atherosclerosis. However, the underlying mechanism by which FFAs result in macrophage apoptosis is not well understood. In cultured human macrophage Thp-1 cells, we showed that palmitate (PA), the most abundant FFA in circulation, induced excessive reactive oxidative substance production, increased malondialdehyde concentration, and decreased ATP levels. Furthermore, PA treatment also led to mitochondrial dysfunction, including the decrease of mitochondrial number, the impairment of respiratory complex IV and succinate dehydrogenase (SDH) activity, and the reduction of mitochondrial membrane potential. Mitochondrial apoptosis was also detected after PA treatment, indicated by a decrease in cytochrome C release, downregulation of Bcl-2, upregulation of Bax, and increased caspase-3 and caspase-9 activity. PA treatment upregulated the expression of adipocyte fatty acid binding protein (A-FABP), a critical regulator of fatty acid trafficking and lipid metabolism. Inhibition of A-FABP with BMS309403, a small-molecule A-FABP inhibitor, almost reversed all of these indexes. Thus, the present study suggested that PA mediated macrophage apoptosis through A-FABP upregulation, which subsequently resulted in mitochondrial dysfunction and reactive oxidative stress. Inhibition of A-FABP may be a potential therapeutic target for macrophage apoptosis and to delay the progress of atherosclerosis.